Kinerja Keuangan Pemerintah Daerah Surabaya melalui Indikator Anggaran Pendapatan dan Belanja Daerah - Clara Rossa Wibisono; Fidela Salsabillah; Revienda Anita Fitrie; Eva Hany Fanida (Journal Social Society, 2026)
Regional autonomy gives local governments broader authority to manage regional resources and finances in order to support development and improve public welfare. As one of Indonesia's largest metropolitan cities, Surabaya has relatively strong fiscal capacity. However, previous studies have generally focused on specific financial ratios and have not comprehensively evaluated the financial performance of the Surabaya City Government using multiple Regional Revenue and Expenditure Budget (APBD) indicators. This study aims to evaluate the financial performance of the Surabaya City Government through APBD indicators during the 2020–2024 period. This research used a quantitative approach with a descriptive method. The study used secondary data obtained from the realization reports of the Surabaya City Government APBD for the 2020–2024 period. Data were collected through documentation and analyzed using regional financial ratios, including the regional independence ratio, effectiveness ratio of Local Own-Source Revenue (PAD), expenditure efficiency ratio, and fiscal decentralization ratio. The study also applied the value for money approach, which emphasizes economy, efficiency, and effectiveness in regional budget management. The results indicate that the financial performance of the Surabaya City Government was generally good, particularly in terms of regional fiscal independence. However, the effectiveness of PAD and expenditure efficiency fluctuated during the observation period. The findings imply that Surabaya has strong fiscal capacity but still needs to improve revenue planning and expenditure control. In conclusion, Surabaya’s financial performance reflects strong regional fiscal independence, although further optimization is required in PAD effectiveness and budget efficiency.